2011
DOI: 10.1186/1472-6920-11-11
|View full text |Cite
|
Sign up to set email alerts
|

A near-peer teaching program designed, developed and delivered exclusively by recent medical graduates for final year medical students sitting the final objective structured clinical examination (OSCE)

Abstract: BackgroundThe General Medical Council states that teaching doctors and students is important for the care of patients. Our aim was to deliver a structured teaching program to final year medical students, evaluate the efficacy of teaching given by junior doctors and review the pertinent literature.MethodsWe developed a revision package for final year medical students sitting the Objective Structured Clinical Examination (OSCE). The package was created and delivered exclusively by recent medical graduates and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 18 publications
7
108
0
1
Order By: Relevance
“…In addition to content learning, peer learners receive emotional support and reassurance that help decrease anxiety and promote greater selfconfidence [2,7]. Rashid, Sobowale, and Gore [14] and Tolsgaard et al [15] compared peer teachers to clinical professors and found no difference in learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to content learning, peer learners receive emotional support and reassurance that help decrease anxiety and promote greater selfconfidence [2,7]. Rashid, Sobowale, and Gore [14] and Tolsgaard et al [15] compared peer teachers to clinical professors and found no difference in learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The idea was to have small numbers of students rotating though different teaching sessions, giving them an opportunity to experience several aspects of life as a foundation doctor. The emphasis was also on near-peer teaching whenever possible, with the potential advantage of receiving guidance from a junior doctor who had only recently passed their final exams but has the experience of being a qualified doctor, and a number of previous studies and observations have supported this notion (Rodriques et al 2009;Rashid et al 2011). …”
Section: Introduction To the Coursementioning
confidence: 86%
“…1 The lack of experience has also been reported to be a key reason for resistance to the introduction of near-peer programs. 34 Another reason may be that neither a peer or near-peer tutor is a content expert or experienced educator. 1,4 Whilst there are challenges, the educational theories and current research suggests that the benefits to implementing near-peer teaching outweigh these challenges.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%